2000
DOI: 10.1080/135457000750020164
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and Home-Based Workers

Abstract: Globalization presents threats to and opportunities for women working in the informal sector. The paper, which draws on the work of Women in Informal Employment: Globalizing and Organizing (WIEGO) Global Markets Program and of HomeNet, focuses on women home-based workers and analyzes, within the framework of global value-chains, the impact of globalization on labor relations and other market transactions. The chains reviewed are: manufactured goods (fashion garments); agricultural products (nontraditional expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 1 publication
1
77
0
3
Order By: Relevance
“…One opportunity, for women to organize themselves in cooperatives, is to buy and share technology that could facilitate an understanding of what product parameters would give their products more access to international markets and potentially help them to gain higher prices for the final product. Carr et al [63], suggested that women as members of associations would also allow them to have links to marketing and new information through information and communication technology. Thus, associations and cooperatives might be logical routes to disseminate such educational videos.…”
Section: Potential Of Ict Use To Enable Empowerment Of Women In a Shementioning
confidence: 99%
“…One opportunity, for women to organize themselves in cooperatives, is to buy and share technology that could facilitate an understanding of what product parameters would give their products more access to international markets and potentially help them to gain higher prices for the final product. Carr et al [63], suggested that women as members of associations would also allow them to have links to marketing and new information through information and communication technology. Thus, associations and cooperatives might be logical routes to disseminate such educational videos.…”
Section: Potential Of Ict Use To Enable Empowerment Of Women In a Shementioning
confidence: 99%
“…In Latin America and South Africa, NTAEs are often produced on large-scale enterprises, with women forming up to 80 percent of the workforce (Carr, Chen, and Tate 2000).…”
Section: Gender and Job Accessmentioning
confidence: 99%
“…This has occurred primarily in female-dominated labor-intensive industries. Women's sequestration in such jobs provides even less bargaining power and we know from research on home workers that the wages women earn in such jobs is little more than half of what they earn in formal sector jobs (Roh 1990;Carr et al 2000;Balakrishnan 2002). …”
Section: Policy and Structural Changes In The 1990smentioning
confidence: 99%